2015
DOI: 10.1089/neu.2015.3918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cortical Thickness after Traumatic Brain Injury in Military Veterans

Abstract: Military service members frequently sustain traumatic brain injuries (TBI) while on active duty, a majority of which are related to explosive blasts and are mild in severity. Studies evaluating the cortical gray matter in persons with injuries of this nature remain scarce. The purpose of this study was to assess cortical thickness in a sample of military veterans with chronic blast-related TBI. Thirty-eight veterans with mild TBI and 17 veterans with moderate TBI were compared with 58 demographically matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…A number of imaging studies have demonstrated cortical thinning in patients with mild, moderate, and severe head trauma primarily in areas involving the frontal, temporal, and parietal cortices . However, none of these studies specifically interrogated associations between PTH burden and cortical thickness patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of imaging studies have demonstrated cortical thinning in patients with mild, moderate, and severe head trauma primarily in areas involving the frontal, temporal, and parietal cortices . However, none of these studies specifically interrogated associations between PTH burden and cortical thickness patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Less Cortical Thickness in Patients With PPTH.-A number of imaging studies have demonstrated cortical thinning in patients with mild, moderate, and severe head trauma primarily in areas involving the frontal, temporal, and parietal cortices. [10][11][12][33][34][35] However, none of these studies specifically interrogated associations between PTH burden and cortical thickness patterns. Potentially indicating time-linked changes in cortical dynamics following concussion, one study 10 found thickening in frontal regions in acutely concussed patients who were imaged less than 2 weeks after suffering motor vehicle-related accidents followed by cortical thinning in the same regions 3 months post-concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity is one of the most common and potentially dangerous symptoms associated with brain injury (Schwarzbold et al, 2010; Adhikari et al, 2011; Logsdon et al, 2014; Michael et al, 2015). Impulsivity is a key finding in patients diagnosed with chronic traumatic encephalopathy (CTE) and presents early in disease progression (Banks et al, 2014; Rebetez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In adult cases of stroke or disorders like multiple sclerosis, subcortical lesions impact regional cortical thickness depending on the area and location of the lesion or infarct 17-21 . In adult TBI reduced cortical thickness has been observed and may be related to injury severity 22, 23 . Whether focal lesions systematically alter cortical development in pediatric TBI has not been previously examined.…”
mentioning
confidence: 99%